2022
DOI: 10.3389/fpls.2022.818206
|View full text |Cite
|
Sign up to set email alerts
|

A High-Quality, Chromosome-Level Genome Provides Insights Into Determinate Flowering Time and Color of Cotton Rose (Hibiscus mutabilis)

Abstract: Hibiscus mutabilis (cotton rose) is a deciduous shrub or small tree of the Malvaceae family. Here, we report a chromosome-scale assembly of the H. mutabilis genome based on a combination of single-molecule sequencing and Hi-C technology. We obtained an optimized assembly of 2.68 Gb with a scaffold N50 length of 54.7 Mb. An integrated strategy of homology-based, de novo, and transcriptome-based gene predictions identified 118,222 protein-coding genes. Repetitive DNA sequences made up 58.55% of the genome, and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…3f , right panel) . Three WGD events have previously been reported in H. mutabilis [ 19 ], and regarding the 4:3 ratio, we speculated that the most recent WGD reported in the H. mutabilis genome was a whole genome triplication (WGT) event that occurred independently after the divergence of okra and H. mutabilis . Fourth, we also calculated the syntenic depth ratio of H. cannabinus vs H. mutabilis , yielding an overall 1:3 pattern ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3f , right panel) . Three WGD events have previously been reported in H. mutabilis [ 19 ], and regarding the 4:3 ratio, we speculated that the most recent WGD reported in the H. mutabilis genome was a whole genome triplication (WGT) event that occurred independently after the divergence of okra and H. mutabilis . Fourth, we also calculated the syntenic depth ratio of H. cannabinus vs H. mutabilis , yielding an overall 1:3 pattern ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a previous study reported two additional WGD events occurring in the H. mutabilis genome [ 19 ]. Interestingly, our results indicate that the most recent WGD event in H. mutabilis was actually a WGT event ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the city flower of Chengdu, H. mutabilis has important historical, cultural, and ornamental value [ 1 ]. H. mutabilis is popular with tourists because of its variety and ability to change colors over the course of one day.…”
Section: Discussionmentioning
confidence: 99%
“…Hibiscus mutabilis is an important ornamental plant from the Malvaceae family that originated in China and has been cultivated in China for more than 2000 years [ 1 ]. As an ornamental plant, H. mutabilis has spread to Japan, Korea, and other countries in Asia.…”
Section: Introductionmentioning
confidence: 99%